2021
DOI: 10.3389/fonc.2021.580455
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Inflammation Attenuates Chemosensitivity and Confers to Poor Survival of Surgical Stage III CRC Patients

Abstract: Background: Heterogeneous clinical and molecular characteristics are reported in colorectal cancer (CRC) with different tumor laterality. However, the outcome of left- and right-sided patients with stage I–III CRC and the role of chronic inflammation in survival differences between them remain unclear.Method: A prospective study including 1,181 surgical patients with stage I–III CRC was carried out to investigate the involvement of circulating fibrinogen-to-pre-albumin (Alb) ratio (FPR) and primary tumor sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These findings are concordant with the results of Dienstmann et al who investigated stage II-III CRC patients and showed a significant decrease in survival rates in stage III CRC patients, which was accompanied by lymph node metastasis [ 15 ]. Furthermore, Ying et al, in their study of 1,181 stage I-III CRC patients, showed that persistent high inflammation levels reduce the effectiveness of chemotherapy and play a role in the unfavorable outlook for individuals with stage III surgical CRC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are concordant with the results of Dienstmann et al who investigated stage II-III CRC patients and showed a significant decrease in survival rates in stage III CRC patients, which was accompanied by lymph node metastasis [ 15 ]. Furthermore, Ying et al, in their study of 1,181 stage I-III CRC patients, showed that persistent high inflammation levels reduce the effectiveness of chemotherapy and play a role in the unfavorable outlook for individuals with stage III surgical CRC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FPR can be used as an indicator to differentiate eligible patients for chemotherapy and predict chemotherapy efficacy [35]. A prospective study of 1181 patients undergoing surgery for stage I-III CRC showed that patients with high FPR had a lower survival rate after chemotherapy than patients with low FPR on the same course of treatment, but better than those who did not undergo chemotherapy after surgical resection, and concluded that chronic high-intensity inflammation could reduce the sensitivity of chemotherapy and lead to a poor prognosis for patients with stage III CRC, providing a basis for targeted anti-inflammatory therapy combined with adjuvant chemotherapy, provide new ideas for the clinical application of targeted anti-inflammatory therapy in patients with high FPR [36].…”
Section: Judgement Of Fib On the Efficacy Of Chemotherapymentioning
confidence: 99%